Pengaruh kompetensi dan transparansi terhadap efektivitas pengelolaan dana kelurahan pada kelurahan di Kecamatan Gubeng Kota Surabaya - Christopher Djamiraga, Axl; Diah Widajantie, Tituk (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to test and prove the effect of competence and transparency on the effectiveness of village fund management in Gubeng District, Surabaya City. This research uses quantitative methods. The sampling technique used is purposive sampling and the type of data in this study is primary data. The sample of this study was 30 employees in 6 villages in Gubeng District, Surabaya City. The data collection technique used in this study was through the distribution of questionnaires or questionnaires to respondents. Technical analysis and hypothesis testing using Partial Least Square (PLS) with SmartPLS 3.0 application software. The results of this study indicate that the competence of the apparatus has a positive and significant effect on the effectiveness of village fund management, as well as transparency which has a positive and significant impact on the management of village funds.